PENGAWASAN KEAMANAN DAN MUTU PANGAN SEGAR ASAL TUMBUHAN (PSAT) DI PEREDARAN DI PROVINSI JAWA TENGAH - Listya Puspitasari; Wawan Riyanto Sulistiono; Lutfi Aris Sasongko (Universitas Wahid Hasyim, 2020)
The research objective is to determine the implementation of the safety and quality inspection of post market Plant Origin Fresh Food(POFF) in Central Java Province and to formulate alternative strategies that can be carried out in inspecting the safety of post market POFFfor consumer protection in the future. The research was carried out from April to September 2020 at the Food Security Board of Central Java Province. The data collected are primary and secondary data. The analysis method used are qualitative descriptive analysis and SWOT analysis. The results showed that the safety and quality inspection of post market POFF was carried out through periodic and special inspecting. The test results showed that the content of biological, chemical and other contaminants on the sample of post market POFF was below the maximum residue/contamination limit. Alternative strategies that can be carried out in inspecting the safety of post market POFF are: (1) carrying out a comprehensive risk analysis; (2) providing education and training for inpectors; (3) adding laboratory testing infrastructure to expand the scope of accredited testing; (4) increasing online socialization and education for consumers; and (5) increasing the inspection of POFF that is circulated online. Keywords: Food Inspection, Postmarket, POFF, SWOT, Central Java